"Alien" Sexuality: Race, Maternity, and Citizenship. (12th January 2013) - Cisneros, Natalie
<x xml:space="preserve">Abstract</x> In this paper, I provide an analysis of the emergence of "problematic of alien sexuality." I first locate discourses about "alien sexuality, " and the so‐called anchor baby in particular, within other national discourses surrounding maternity, the fetus, and citizenship. I analyze the ways that national political discourses surrounding "anchor babies" and "alien maternity" construct the "problematic of alien sexuality, " thus constituting the "alien" subject as always‐already perverse. I suggest that this production of a sexually deviant and threatening "alien" subject functions in the normative dichotomy that places the sexually pure citizen on the one hand, and the perverse anticitizen on the other, in what I call "backwards uncitizening." My analysis of this process shows that the perverse "alien" subject, as constituted in significant part by nonjuridical normalizing mechanisms of biopower, resists the juridical discourse that is supposed to determine it.